Modelo de gestión por procesos, como herramienta para mejorar la productividad de Avícola Verónica - Benites Panchi, Verónica Magaly (2023)
The present research work proposed to develop a process management model as a tool to improve the productivity of Avícola Verónica, due to the fact that problems were diagnosed in the company such as: the non-existence of the mission, vision, deficient quality control of the production, lack of staff training, did not have productivity indicators. A qualitative-quantitative methodology and a descriptive exploratory type of research were used, the total population corresponded to 25 people, 10 poultry employees and 15 strategic clients. The technique applied for the collection of information was the observation and analysis of data, for which three research instruments were used: A survey applied to the employees of the poultry farm, an interview directed to the administrative area and a survey applied to the clients. . It began by analyzing the current situation of the company and after making a recognition and finding the most critical process and proposing actions to improve the processes, including institutional organization chart, SWOT, mission, vision, organizational values and the process management model with indicators of efficiency and effectiveness that allow to measure the fulfillment of goals of the small company, thus the results were obtained: the added value to satisfy the needs of the client increased by 30.79% and productivity increased by 0.13 times its current value, with this concludes that the proposal for the implementation of a process management model for Avícola Verónica is essential to promote good administration and the use of resources.